Aggressive pituitary adenomas occurring in young patients in a large Polynesian kindred with a germline R271W mutation in the AIP gene - Jennings, Juliet E; Georgitsi, Marianthi; Holdaway, Ian; Daly, Adrian F; Tichomirowa, Maria; Beckers, Albert; Aaltonen, Lauri A; Karhu, Auli; Cameron, Fergus J (European journal of endocrinology, 2009)
ObjectiveMutations in the aryl hydrocarbon receptor-interacting protein (AIP) were recently shown to confer a pituitary adenoma predisposition in patients with familial isolated pituitary adenomas (FIPA). We report a large Samoan FIPA kindred from Australia/New Zealand with an R271W mutation that was associated with aggressive pituitary tumors.Design and methodsCase series with germline screening of AIP and haplotype analyses among R271W families.ResultsThis previously unreported kindred consisted of three affected individuals that either presented with or had first symptoms of a pituitary macroadenoma in late childhood or adolescence. The index case, a 15-year-old male with incipient gigantism and his maternal aunt, had somatotropinomas, and the maternal uncle of the index case had a prolactinoma. All tumors were large (15, 40, and 60 mm maximum diameter) and two required transcranial surgery and radiotherapy. All three affected subjects and ten other unaffected relatives were found to be positive for a germline R271W AIP mutation. Comparison of the single nucleotide polymorphism patterns among this family and two previously reported European FIPA families with the same R271W mutation demonstrated no common ancestry.ConclusionsThis kindred exemplifies the aggressive features of pituitary adenomas associated with AIP mutations, while genetic analyses among three R271W FIPA families indicate that R271W represents a mutational hotspot that should be studied further in functional studies.